PEMEROLEHAN BAHASA PADA ANAK SUKU SASAK DALAM PERSPEKTIF PSIKOLINGUISTIK - Prasetiawan, Deny (Jurnal Pendidikan Bahasa dan Sastra, 2017)
Language acquisition is the process of understanding and production of language in children through several stages ranging from groping to fluent talk. This study aims to assess the ability of children aged four years and five months in (1) to understand basic vocabulary; (2) describes the acquisition of the first language on a phonological level, and; (3) the acquisition of language on a syntactic level. The method used in this research is the method of referring, proficient, and documentation. This research uses psycholingistic approach. This psycholinguistic approach tries to explain the essence of the structure of language, and how it is acquired, used at the time of speech, and at the time of understanding the sentences in the narrative. In essence in the activities of communication occurs the process of producing and understanding speech. The results of this study of language acquisition on the phonological level and the syntax among the respondents of the study is good enough in speaking, and there are no significant deviations in the resulting speech. Language acquisition of children aged four years and five months is at the stage of the development of a sentence. Respondents have been familiar with the pattern of dialogue, have understood when it was his turn to speak and when it was his turn to speak. Respondents have mastered the basic grammar laws of adults, developing vocabulary, and phonological development can be said to have ended. However, respondents still have difficulty in pronunciation of some consonants.Keywords: language acquisition, psycholinguistics, phonology, syntax